PENGARUH KONSENTRASI DAN FREKUENSI PEMBERIAN PUPUK ORGANIK CAIR LIMBAH TAHU TERHADAP PERTUMBUHAN DAN HASIL TANAMAN SELADA (Lactuca sativa L.) - Rismalati, Dewi; Rusmana, Rusmana; Sulistyorini, Endang; Utama, Putra (Fakultas Pertanian, Universitas Janabadra, 2024)
The use of liquid organic fertilizer is an alternative to substitute the use of inorganic fertilizer. Liquid organic fertilizer from tofu waste can be an alternative, but it is necessary to research the appropriate concentration and frequency of administration. This research aims to determine the effect of concentration and frequency of application of liquid organic fertilizer from tofu waste on the growth and yield of lettuce plants (Lactuca sativa L.). This research was structured in a Randomized Block Design with two factors. The first factor is concentration which consists of 4 levels, namely T0: 0 ml/l, T1: 200 ml/l, T2: 300 ml/l, and T3: 400 ml/l. The second factor is frequency consisting of three levels, namely F0: once every 5 days, F1: once every 7 days, and F2: once every 9 days. The results of the research showed that giving liquid organic fertilizer from tofu waste with different concentrations had an effect on plant height, number of leaves and area of lettuce leaves. Providing liquid organic fertilizer from tofu waste with different frequencies had no effect on all observed variables. There was an interaction between treatment concentration and frequency of giving tofu waste POC to lettuce plants. A concentration of 300 ml/l with a frequency of administration once every seven days shows the best results. Keyword: lettuce, concentration, frequency INTISARIPenggunaan pupuk organik cair menjadi alternatif untuk mensubstitusi penggunaan pupuk anorganik. Pupuk organik cair dari limbah tahu dapat menjadi satu alternatif, namun perlu diteliti berapa konsentrasi dan frekuensi pemberian yang tepat. Penelitian ini bertujuan untuk mengetahui pengaruh konsentrasi dan frekuensi pemberian pupuk organik cair limbah tahu terhadap pertumbuhan dan hasil tanaman selada (Lactuca sativa L.). Penelitian ini disusun dalam Rancangan Acak Kelompok dengan dua factor. Faktor pertama adalah konsentrasi yang terdiri dari 4 taraf yaitu T0: 0 ml/L, T1: 200 ml/L, T2: 300 ml/L, dan T3: 400 ml/L. Faktor kedua adalah frekuensi terdiri dari tiga taraf yaitu F0: 5 hari sekali, F1: 7 hari sekali, dan F2: 9 hari sekali. Hasil penelitian menunjukkan bahwa Pemberian pupuk organik cair dari limbah tahu dengan konsentrasi yang berbeda berpengaruh terhadap tinggi tanaman, jumlah daun, dan luas daun selada. Pemberian pupuk organik cair dari limbah tahu dengan frekuensi berbeda-beda tidak berpengaruh terhadap semua variabel pengamatan. erdapat interaksi antara perlakuan konsentrasi dan frekuensi pemberian POC limbah tahu pada tanaman selada. Konsentrasi 300 ml/l dengan frekuensi pemberian tujuh hari sekali menunjukkan hasil terbaik. Kata kunci: selada, konsentrasi, frekuensi